Vulnerabilities perceived by men in the context of the Covid-19 pandemic - Anderson Reis de Sousa; Thiago da Silva Santana; Evanilda Souza de Santana Carvalho; Isabel Amélia Costa Mendes; Milena Bitencourt Santos; Jean Limeira Reis; Adailson Vieira da Silva; Álvaro Francisco Lopes Sousa (Universidade Federal do Ceará, 2021)
Objective: to understand the vulnerabilities perceived by men in the context of the Covid-19 pandemic. Methods: socio-historical, qualitative study, carried out from the results of online research in all regions of Brazil. The sample consisted of 200 men. The data were processed and analyzed methodologically by the Collective Subject Discourse, supported by the framework of epidemic disease. Results: men perceived the vulnerabilities due to the existence of chronic diseases in them and in the family, the need to maintain a work routine that limits the adoption of social distance, the uncertainties generated by the pandemic, which threatens the maintenance of employment and the professional achievement projects, in addition to the discomfort caused by the interruption of sexual interactions. Conclusion: men's perceptions of vulnerabilities in the pandemic revolved around health, professionalization, work and sexuality.